IMPROVING THE RESULTS OF STUDENTS FREE POETRY WRITING SKILLS USING STRATEGI TULIS KINI, DI SINI - Dwi cahyadi wibowo; Betty Nur Dwi Jayanti; Valentinus Ola Beding (STKIP Persada Khatulistiwa Sintang, 2019)
The background of the problem in this study is the low interest of students in writing because they consider writing to be unpleasant, students' low understanding of the material, many students find it difficult to write free poetry, low strategies, models, or learning methods and learning media used by teachers less interesting and fun that makes students pay less attention to lessons while in class.The purpose of this study was to improve the improvement of poetry writing skills freely using the current writing strategy, here in class V B of State Elementary School 23 Clogging the 2018/2019 school year. The form of this research is classroom action research carried out in two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection.The subjects of the study were students of class V B of Elementary School 23 menyumbung which amounted to 23 students. Data sources came from class V B students, V B grade teachers, learning activities and documents. To collect data used observation sheets, test questions and student interview sheets. The results of class action research show that the current writing strategy, here can significantly improve students' free poetry writing skills. Student learning outcomes in the first cycle of all the questions given obtained an average value of 64.22. In the second cycle of the overall questions given an average value of 70.68 was obtained so that the average increase of 6.46 was obtained. And the students' response to the strategies used was easy to understand and fun. So it can be concluded that there was an increase in poetry writing skills. free to use the current write strategy, here.